Pembelajaran Membaca Solmisasi pada Siswa Kelas X Minat Vokal dengan Metode Solfegio di SMA N 9 Kupang - Vinsensius Yosep Manek; Mersiana Rafu; Maria Ayustika Tai; Maria Florida Bupu; Yoseph Copertino Ancis; Kadek Paramitha Hariswari (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2025)
Solmization is a system used in reading number notation or what is commonly called a naming system for each note in a diatonic scale. The problem that occurs in SMAN N 9 Kupang is that in singing they tend to imitate the notes that are exemplified without understanding the notation. The main problem in this study is how the process of implementing the solfegio method in learning to read solmization for vocal students of class X of SMA N 9 Kupang. The purpose of this study is to describe the process of implementing the solfegio method in learning to read solmization for vocal students of class XI of SMAN N 9 Kupang. The approach in this study is a qualitative approach with a field action method. The results of the study describe the process of learning to read solmization which is carried out in 3 stages, namely the initial stage, the core stage and the final stage, which are described during 10 meetings. The final result of this study is that students are able to read number notation well, understand the value of notation, notation symbols, signs in number notation that can be observed through the observation rubric that the researcher has created. During the learning process of reading solmization, some students had difficulty in understanding the value of the notes on the 1/16 note, but these difficulties can be overcome by using the solfeggio method and the researcher providing repeated exercises.